About the lectures on jazz by the musician baltasar samper : An approach to the didactics of swing - Vicens Vidal, Francesc (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In 1935 Baltasar Samper gave several conferences on jazz in Barcelona. The recovery of the texts of these conferences allow us to highlight the didactic dimension of the composer in a cultural context which was marked by academicism. However, Samper’s efforts to spread jazz music among his colleagues, who considered jazz a stigmatized music, will give rise to content that lives up to the postulates of the Parisian Hugues Panassié. This contribution concludes by verifying of the Samperian teachings on jazz and suggesting its continuity in current didactic contexts.